Cardiovascular magnetic resonance phase contrast imaging - Krishna S. Nayak; Jon‐Fredrik Nielsen; Matt A. Bernstein; Michael Markl; Peter Gatehouse; René M. Botnar; David Saloner; Christine H. Lorenz; Han Wen; Bob S. Hu; Frederick H. Epstein; John N. Oshinski; et al. (2015)
Cardiovascular magnetic resonance (CMR) phase contrast imaging has undergone a wide range of changes with the development and availability of improved calibration procedures, visualization tools, and analysis methods. This article provides a comprehensive review of the current state-of-the-art in CMR phase contrast imaging methodology, clinical applications including summaries of past clinical performance, and emerging research and clinical applications that utilize today's latest technology.